THEMATIC INTERPRETATION AS AN INTEGRATIVE ‎EPISTEMOLOGICAL MODEL FOR CONTEMPORARY ‎ISLAMIC RELIGIOUS EDUCATION - Fadly, Ahmad; Kustati, Martin; Bashori (As-Sulthan Journal of Education, 2025)
The rapid advancement of contemporary sciences often neglects ethical and spiritual foundations, creating a gap between scientific progress and Qur’anic guidance. Previous studies on tafsir maudhu’i have focused on methodology and thematic application but have not systematically developed an integrative epistemological model relevant to Islamic education. This study aims to formulate the Integrative Epistemology of Tafsir Maudhu’i as a conceptual framework for bridging revelation with modern sciences and educational practices. Employing a qualitative library research design, the study analyzes classical tafsir, contemporary exegetical works, and recent scholarly contributions, supported by descriptive, comparative, and normative-contextual analysis. The findings reveal that tafsir maudhu’i integrates normative Qur’anic values, epistemological principles, and practical applications in addressing contemporary challenges such as artificial intelligence ethics, bioethics, environmental sustainability, and religious pluralism. The research advances tafsir studies by introducing a new epistemological model that unites text, reason, and social reality. This model offers practical guidance for Islamic Religious Education curricula, policymaking, and interdisciplinary dialogue between religion and science. The study concludes that tafsir maudhu’i is not merely a hermeneutical method but also an alternative epistemology capable of renewing Islamic thought and contributing to global ethical discourse.